A prototype design to maintain temperature and humidity in an open compound restaurant - Sharif, Md. Raihan; Ullah, Mohammad Habib; Muhida, Riza (EuroJournals Publishing, Inc., 2011)
This paper presents the design and development of a prototype to control temperature and humidity in a restaurant. The system involves mechanical part as well as the control mechanism. When the temperature and humidity of the open compound restaurant is detected more or less than the range provided, it will send a signal to the controller. The information sends to the outputs which are fan, motor, and booster pump. Therefore, when the humidity decreases, the mist water turns on. While the temperature increases, the speed of motor also increases. Microcontroller is used as a decision maker replacing the conventional system.